Eksplorasi Pengelolaan Sarana dan Prasarana dalam Upaya Peningkatan Mutu Pelayanan Rumah Sakit: Studi Kualitatif - Candra, Adi; Haninun, Haninun (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the management of health facilities and infrastructure, identify supporting and inhibiting factors, and examine the influence of facility and infrastructure management on service quality at the Anugerah Medical Center Metro Lampung Maternity and Child Hospital (RSIA). The study uses a qualitative approach with descriptive methods. Data collection was conducted through in-depth interviews, direct observation, and documentation studies with purposively selected informants, including elements of management, health workers, administrative staff, and patients or patient families. Data validity was guaranteed through source and technical triangulation. The results of the study indicate that the management of facilities and infrastructure at the Anugerah Medical Center Metro Lampung Maternity and Child Hospital has been implemented systematically through the stages of planning, procurement, maintenance, and supervision and evaluation, although not yet fully optimal. The main supporting factors include the hospital management's commitment to improving service quality and patient safety, as well as internal policy support. Meanwhile, inhibiting factors are more technical and managerial in nature, such as the time-consuming procurement administration process, limited human resources specifically for facility maintenance, and suboptimal cross-unit coordination. The management of facilities and infrastructure has been shown to significantly impact service quality, particularly in terms of service effectiveness, patient comfort, and healthcare worker performance. The conclusion of this study indicates that the management of facilities and infrastructure is a crucial component in supporting the quality of healthcare services at the Anugerah Medical Center Metro Lampung Hospital. Therefore, it is recommended that the hospital strengthen short-term and long-term planning, optimize the integrated electronic inventory system, improve the competency of human resource facility managers, and strengthen cross-unit coordination and supervision to ensure the sustainability of the quality of maternal and child healthcare services.